Features of Shakespeare’s works interpreted by the Russian translator Dmitry Minh - Olga S. Milotaeva, Dmitry N. Zhatkin, (Opción, 2019)
The article is devoted to consideration of features of Shakespeare’s works interpreted by the Russian translator Dmitry Egorovich Minh. In the course of the analysis social, cultural, comparative, historical and typological methods are used. As a result, appearance of complete translations of Richard II, created by V.D. Kostomarov and A. L. Sokolovsky in 1865, led to stopping D.E. Minh’s work on his interpretation of the chronicle Richard II. In conclusion, he was significantly late in comparison with A.V. Druzhinin and A.L. Sokolovsky’s translations which had appeared in the middle of the 1860s. Therefore D.E. Minh’s work remained unnoticed by public.